(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
This scientific article provides a comprehensive review of improving the possibilities of preparing future educators for spiritual and educational activities based on axiological approaches. Axiology, as a branch of philosophy, focuses on the study of values and their significance in human life. Recognizing the importance of values in education, this article explores how axiological approaches can enhance the preparation of future educators for their spiritual and educational roles. The article examines the theoretical foundations of axiology in education, discusses the integration of values in teacher preparation programs, and explores practical strategies for fostering spiritual and educational growth. Furthermore, it highlights the benefits of axiological approaches and provides recommendations for educators and policymakers to effectively incorporate them into the preparation of future educators.